New technologies in the field of low-moisture block manufacturing and supplementation - Miller, Kevin Alan (Kansas State University, 2012)
Three studies were conducted to investigate alternative ingredients and processing methods for manufacturing low-moisture blocks. Study 1 was designed to determine if ruminal lactate could be transiently increased by feeding fructose-based blocks to heifers fed prairie hay, thus providing substrate for establishment of lactate utilizing microbes. Low-moisture blocks comprised of 96% fructose and 4% vegetable oil (DM basis) were manufactured and dosed via ruminal fistulas. Administration of fructose blocks resulted in transient increases in ruminal lactate (P < 0.05), accompanied by transient decreases in pH (P < 0.05). Ruminal fluid incubated with semi-defined lactate medium became more turbid (P < 0.05) as a result of prior exposure to fructose blocks suggesting greater capacity for lactate metabolism. In study 2 a portion of the molasses was replaced by corn steep liquor (CSL) or condensed corn distiller’s solubles (CCDS). Heifers were fed a forage-based diet and supplemented with 1 of 4 supplement blocks. Supplements were a 30% CP molasses block manufactured at ambient pressure and high temperatures (Mol-30). The remaining treatments were manufactured at reduced pressure and temperature and were a 30% CP block with 36% CSL (CSL-30); a 40% CP block with 40% CSL (CSL-40); or a 40% CP block with 25% CCDS (CCDS-40). Supplementing with Mol-30 and CSL-40 resulted in greater DMI (%BW) than with CCDS-40 (P < 0.05). Supplementing with CSL-30 improved efficiency and ADG compared to Mol-30 (P < 0.01). Study 3 evaluated the affect of cooking temperature on blocks containing CSL fed to heifers receiving a forage-based diet. Heifers were offered no supplement (Control) or a 15% CSL block manufactured at ambient pressure and high temperature (HT-15). The remaining treatments were manufactured at reduced pressure and temperature and were a 15% CSL block (LT-15); or 40% CSL block (LT-40). Control heifers had the lowest DMI and LT-40 had the greatest (P < 0.05). Feeding heifers LT-15 or LT-40 improved ADG compared to heifers fed HT-15 or no supplement (P < 0.05). Heifers fed LT-40 tended to be more efficient than those fed HT-15 and Control (P = 0.07).
Keywords: Forage; Low-moisture blocks; Lactic acid; Animal Sciences (0475)